A quantum chemical analysis of Zn and Sb doping and co-doping in SnO2 - Luis Villamagua (AIP Advances, 2017)
This work presents a quantum chemical study of Zn and Sb doping and co-doping in SnO2 carried out by a DFT+U method. The analysis has been developed by introducing three different modifications in the otherwise pure SnO2 system. In the first place, an oxygen vacancy was introduced within the crystal. Following, such a system was doped (separately) by Zn or Sb impurities. Finally, the best energetic positions for both Zn and Sb atoms were simultaneously introduced within the lattice. Results of the simulations show that the confined charge that appeared due to the introduction of the oxygen vacancy interacts with the dopants atoms, being this interaction mostly responsible of the observed effects, i.e., EG shrinkage, F-centers formations, and magnetic momentum rise.